A simplified space-vector modulation algorithm for four-leg NPC converters - Rojas, Felix; Cardenas, Roberto; Kennel, Ralph; Clare, Jon C.; Diaz, Matias (IEEE, 2016)
To interface generation sources and loads to four-wire distribution networks is important to use power converters and modulation methods which provide high performance, flexi¬bility and reliability. To achieve these goals, this paper proposes a simple and efficient Space Vector Modulation (SVM) algorithm in α3-y coordinates for Neutral Point Clamped (NPC) converters. The proposed SVM method reduces a three-dimensional (α3-y) search of the modulating vectors into a simple two-dimensional (α3) problem. Moreover, the algorithm provides full utilisation of the dc-link voltage, full utilisation of the redundant vectors and it can be applied to any other four-leg converter topology. The proposed SVM has been successfully validated using a 6kW three-level four-leg NPC converter, achieving control over the voltages of the dc-link capacitors and simple definition of switching pattern for shaping frequency spectrum.